Diagnostic Accuracy of Chest Ultrasonography for Post-traumatic Pneumothorax Taking CT scan as Gold Standard - Zafar, Amna; Bano, Arjumand; Zahid, Alishba; Maryam, Javeria; Sadiq, Nosheen; Latif, Atif (Indus Journal of Bioscience Research, 2025)
Objective: To determine the diagnostic accuracy of chest ultrasonography for detecting post-traumatic pneumothorax, using high-resolution CT scan as gold standard. Study design: Cross-sectional validation. Place and duration of study: Department of Diagnostic Radiology, CMH Multan from Nov, 2024 to Apr, 2025. Methodology: A total of 150 patients aged ≥18 to ≤65 years, referred to the department with clinical signs of pneumothorax were included in the study. Patients underwent chest ultrasonography for detecting post-traumatic pneumothorax based on key sonographic signs. A high-resolution CT scan of the thorax was then performed within three hours of ultrasonography. Diagnostic accuracy was then calculated by determining sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy and a 2×2 contingency table was constructed keeping CT scan as gold standard. Results: Mean age of patients was 36.85±9.61 with age range of 23 to 64 years. Number of male patients was higher (76%) in overall study population compared to females (24%). The diagnostic accuracy parameters for detecting pneumothorax demonstrated high sensitivity (87.27%), specificity (96.84%), positive predictive value (94.12%), negative predictive value (92.93%), and overall diagnostic accuracy (93.33%) of chest ultrasonography keeping CT scan as gold standard. Conclusion: Chest ultrasonography provides high sensitivity, specificity, and predictive values offering a reliable alternative where immediate CT access is difficult or not feasible.